PENERAPAN DATA MINING DENGAN METODE NAIVE BAYES CLASSIFIER PADA PENJUALAN BARANG UNTUK OPTIMASI STRATEGI PEMASARAN - Lubis, Kahfi Rama Putra; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2023)
Along with technological developments, market developments are also increasing rapidly and competition is starting to occur between entrepreneurs and business people, which requires entrepreneurs to take advantage of existing technology. At this time the Universal Homeware Store does not realize that this data can be processed effectively to find out the development of a business or business that is being run, besides that the procurement of goods that customers need is often unavailable. One of the data processing technologies is by applying data mining. Data mining is a form of extracting information from data that is large enough to obtain data patterns so as to produce information data that is useful for making decisions and increasing profits in developing marketing strategies. One of the uses of data mining is using the Naive Bayes Classifier algorithm. Naive Bayes Classifier is one of the existing algorithms in data mining which is used to deal with uncertainty problems by emphasizing the concept of probability of use and measuring the level of accuracy so that it can predict purchasing strategies from past sales analysis. with research results Using 36 data and with rapid minner tools produces an accuracy value of 80%